Antidumping nas Américas: Uma investigaç\~ao dos efeitos do uso desse instrumento sobre as exportaç\~oes e sobre a conduta das empresas brasileiras - Marta dos Reis Castilho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– Brazil is one of the ten countries most cited in antidumping processes in the world and this explains the Brazilian government's efforts on discussing the antidumping rules in several multilateral forms. This paper investigates the effects of these measures on Brazilian export performance in two ways. First, we characterize the strategies of Brazilian firms that are cited in antidumping processes. Secondly, we seek to estimate the effects of antidumping measures on Brazilian export flows. We concentrate our analysis on selected countries of the American continent as they are not only important trade partners of Brazil, but are also responsible for 70% of processes initiated against Brazil in the period of 1989 to 2004.
Keywords: F13; 330; Antidumping; Export; Brasilien